Plasma D-dimer predicts short-term poor outcome after acute ischemic stroke. - Xiao-Ying Yang; Shan Gao; Jie Ding; Yan Chen; Xing-Sheng Zhou; Jing-E Wang (PLoS ONE)
Objective Haemostatic biomarkers associated with poor outcome in acute ischemic stroke (AIS). The objective of the study was to evaluate the predictive value of plasma D-dimer (D-D) on functional outcome at 90-day follow-up from stroke onset. Methods We conducted a prospective, observational cohort study in the emergency department and enrolled 220 patients with AIS. Plasma D-D concentrations, determined by a particle-enhanced, immunoturbidimetric assay, were measured. Each patient's medical record was reviewed, and demographic, clinical, laboratory and neuroimaging information was abstracted. Results There was a positive correlation between levels of D-D and the NIHSS (r = 0.361, p<0.001), and the infarct volume (r = 0.449, p<0.001). In the 69 patients with an unfavorable functional outcome, D-D levels were higher compared with those in patients with a favorable outcome [3.24(IQR, 2.18-4.60)mg/L vs 0.88(IQR, 0.35-1.77) mg/L; p<0.001]. After adjusting for all other significant outcome predictors, D-D level remained an independent predictor for unfavorable functional outcome and mortality with an odds ratio of 2.18 (95% CI, 1.55-2.83), 3.22 (95% CI, 2.05-6.43); respectively. Conclusions D-D levels are a useful tool to predict outcome and mortality 90-day after acute ischemic stroke and have a potential to assist clinicians.